Discovery of an X-Ray Photoionized Optical Nebula and a Radio Nebula Associated with the ULX NGC 4861 X-1 - Hang Gong; Ryan Urquhart; Alexandr Vinokurov; Yu Bai; Antonio Cabrera-Lavers; Sergei Fabrika; Liang Wang; Jifeng Liu (The Astrophysical Journal, 2023)
We have conducted long-slit spectroscopic observations and analyzed archival radio data for the ultraluminous X-ray source (ULX) NGC 4861 X-1. Our spectral line analysis unveils NGC 4861 X-1 as the fourth ULX situated within an X-ray photoionized nebula, following three previous findings made approximately two decades ago. Remarkably, we discover NGC 4861 X-1 also possesses a radio nebula emitting optically thin synchrotron radiation, which contradicts its X-ray photoionization and raises doubts about the four ULXs being a mere coincidence. Instead of gradually accumulating from different bands bit by bit, our multiband discovery is made all at once. Moreover, we tentatively perceive a faint continuum spectrum of the optical nebula. Further observations are needed to ascertain its radio structures and verify the optical continuum.